The Impact of Posner Strategy in Modifying the Misconceptions in Chemistry among Female Tenth Graders in Jordan - Altawalbeh, Khitam; Khatybeh, Abdalla; Almomani , Idrees (Dirasat: Educational Sciences, 2020)
This study aims at revealing the impact of teaching according to Posner’s strategy in modifying of some concepts in chemistry for 10th grade female students. The quasi-experimental design was chosen to achieve the purposes of the study. The sample consisted of (30) female students as an experimental group which was taught using Posner's strategy, and (30) female students as a control group which was taught using traditional method. The test was consisted of (20) items of Two-Tier Multiple Choice questions, and it was applied before and after to both groups. After data collection, SPSS for statistical analysis was used. The results showed that the students had misconceptions in chemistry. Also the results revealed the presence of statistically significant differences between the mean scores of the two groups, in favor of the experimental group which was taught using to Posner’s strategy. This confirms the effectiveness of Posner’s strategy in modifying chemistry misconceptions. In light of the results, it was recommended to use Posner’s strategy in teaching, and training teachers on it.